Strengthening Fiscal Capacity and Investment Spending for Enhanced Public Financial Performance - Budi Hendaris , Raden; Zulfikar , Rudi; Muchlis, Munawar; Yusiva Ibrani, Ewing (International Journal of Accounting and Economics Studies, 2025)
This study uses empirical evidence to examine the effect of fiscal capacity and investment spending on subnational financial performance in ‎a decentralized public finance system that relies heavily on transfers. The panel data and estimation strategy yielded three key results. Firstly, ‎it is evident that revenue capacity, when owned in-house, is consistently linked to favourable financial outcomes. This underscores the pivotal role that revenue autonomy plays in fostering incentives for financial prudence and sustainable budget management. Secondly, invest-‎ment spending has been shown to positively impact fiscal performance, indicating that public investment can serve as an effective long-term ‎stabilizer for fiscal management, provided that there is sufficient institutional capacity. Thirdly, intergovernmental transfers have a detriental effect on financial performance, significantly undermining the fiscal stimulus of own-source revenue. This suggests soft budget con-‎constraints and distorted fiscal incentives under dependent transfers. Transfers do not have a significant impact on the relationship between ‎capital expenditure and investment effectiveness. This suggests that investment effectiveness is more influenced by internal managerial com-‎competencies than financial form characteristics. The results demonstrate that subnational fiscal performance is influenced by a number of factors. These include internal fiscal capacity, investment decisions, and the incentive properties of intergovernmental fiscal arrangements. The ‎paper makes a valuable contribution to the literature by explaining how transfer dependence affects the efficiency of local fiscal tools and by ‎providing relevant policy implications for building up fiscal resilience in centralized systems.
Keywords: Public Investment; Intergovernmental Transfers; Subnational Finance; Fiscal Performance